Zastosowanie controllingu w powszechnych towarzystwach emerytalnych - Prudzienica-Grunt, Maja (Applied to controlling in general pension fund societies, 2006)
Controlling is an instrument of management and at the same time it is an element of organization’s structure which uses different methods and techniques of planning and control. Therefore a question can be posed what place the controlling has in the system of management organization in PTEs (PTE can be translated as: pension fund company). Considering the results of the analysis presented in this text we can say that controlling develops as a management subsystem in these types of institutions. So it becomes a comprehensive and co-ordinated management operation with the main aim to amass the capital of pension fund's members. In addition, it helps to ensure the existence and development of PTE while at the same time it affects the building of pension fund's members’ confidence.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 127-137